Different Profiles of Spatial Navigation Deficits In Alzheimer’s Disease Biomarker-Positive Versus Biomarker-Negative Older Adults With Amnestic Mild Cognitive Impairment - Laczó, Martina; Martinkovic, Lukas; Lerch, Ondrej; Wiener, Jan M.; Kalinova, Jana; Matuskova, Veronika; Nedelska, Zuzana; Vyhnalek, Martin; Hort, Jakub; Laczó, Jan (Frontiers in Aging Neuroscience, 2022)
Background: Spatial navigation impairment is a promising cognitive marker of Alzheimer’s disease (AD) that can reflect the underlying pathology. Objectives: We assessed spatial navigation performance in AD biomarker positive older adults with amnestic mild cognitive impairment (AD aMCI) versus those AD biomarker negative (non-AD aMCI), and examined associations between navigation performance, MRI measures of brain atrophy and cerebrospinal fluid (CSF) biomarkers. Methods: 122 participants with AD aMCI (n=33), non-AD aMCI (n=31), mild AD dementia (n=28) and 30 cognitively normal older adults (CN) underwent cognitive assessment, brain MRI (n=100 had high quality images for volumetric analysis) and three virtual navigation tasks focused on route learning (body-centered navigation), wayfinding (world-centered navigation) and perspective taking/wayfinding. Cognitively impaired participants underwent CSF biomarker assessment (amyloid-β1-42, total tau, and phosphorylated tau181 [p-tau181]) and amyloid PET imaging (n=47 and n=45, respectively), with a subset having both (n=19). Results: In route learning, AD aMCI performed worse than non-AD aMCI (p<.001), who performed similarly to CN. In wayfinding, aMCI participants performed worse than CN (both p≤.009) and AD aMCI performed worse than non-AD aMCI in the second task session (p=.032). In perspective taking/wayfinding, aMCI participants performed worse than CN (both p≤.001). AD aMCI and non-AD aMCI did not differ in conventional cognitive tests. Route learning was associated with parietal thickness and amyloid-β1-42, wayfinding was associated with posterior medial temporal lobe (MTL) volume and p-tau181 and perspective taking/wayfinding was correlated with MRI measures of several brain regions and all CSF biomarkers. Conclusion: AD biomarker positive and negative older adults with aMCI had different profiles of spatial navigation deficits that were associated with posterior MTL and parietal atrophy and reflected AD pathology.